Pengaruh Kemasan terhadap Mutu Choux Pastry Kering yang Disubstitusi Konsentrat Protein Ikan Gabus: Effect of Packaging on the Quality of Dry Choux Pastry Substituted with Fish Protein Concentrates of Snakehead Murrel - Esthy Rahman Asih; Yuliana Arsil (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Dry choux pastry substitution of fish protein concentrates snakehead has a high protein and fat content. This high protein and fat content can support the physical and chemical deterioration during storage. Proper handling of this choux pastry can prevent relapse. This study aimed to measure the effect of packaging on the quality of dry choux pastry by substituting the fish protein concentrates of snakehead at 26-29oC for 56 days. This research is an experimental study with a completely randomized design (CRD) with two treatment factors, namely the type of packaging (aluminum foil and polypropylene plastic) and storage time (14, 28, 42, and 56 days). In this study, dry choux pastry was stored in aluminum foil and polypropylene plastic packaging and was observed for 14, 28, 42, and 56 days of storage. Storage is carried out using the ESS (Extended Storage Studies) method. Data were analyzed using a one-way ANOVA statistical test with a 95% confidence level. If there is a difference, continue testing with DMRT at the 5% level. Dry choux pastry with aluminum foil and polypropylene plastic packaging for 56 days of storage. There was no significant difference in the attributes of color, taste, and aroma, but significantly different in terms of texture. There was a high water content, peroxide value, and free fatty acids in the dry choux pastry with the more extended storage time. Aluminum foil packaging is better used as a package for dry choux pastry than polypropylene plastic packaging seen from the dry choux pastry texture, water content, peroxide value, and free fatty acid during storage.